Eyebrow tattoo-associated sarcoidosis: A case report - Nie, Shu; Li, Ke; Gao, Chuang; Yin, Na; Chen, Zile; Wu, Zhouwei (Frontiers in Medicine, 2022)
Cutaneous sarcoidosis can manifest after doing a permanent makeup (PMU), such as tattooed eyebrows. A 41-year-old Chinese woman, with a tattoo in the eyebrows, developed yellow–brown plaques in her eyebrows for several months. A dermatopathological examination revealed non-caseating granulomas consistent with cutaneous sarcoidosis. For months, topical corticosteroids were applied, which showed little effect. Furthermore, a physical evaluation of the patient revealed no apparent involvement of other body organs except bilateral hilar lymphadenopathy with few diffuse reticulonodular opacities. On the basis of fully informed consent, the patient agreed to a 6-month initial follow-up to avoid unnecessary PMU.